Pengaruh Media Pembelajaran Articulate Storyline Terhadap Hasil Belajar Peserta Didik pada Pembelajaran Matematika di Kelas VIII SMP Negeri 5 Padang Panjang - Zahra Halwy Zakiya; Aniswita; Haida Fitri; Iltavia (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the low mathematics learning outcomes of class VIII students of SMP Negeri 5 Padang Panjang, which is indicated by the failure to achieve the minimum mastery limit. Initial observations indicate that the low activity and participation of students in learning are related to the use of learning media that are still conventional and less interactive. This study aims to determine the effect of the use of Articulate Storyline learning media on the mathematics learning outcomes of class VIII students of SMP Negeri 5 Padang Panjang. The type of research used is experimental research with the Static Group Comparison Design. The research population includes all class VIII students, with sampling using a random sampling technique. Class VIII.2 was designated as the experimental class and class VIII.5 as the control class. Research data were collected through a mathematics learning outcome test that has been tested for validity and reliability. Data analysis was carried out using the t-test with the help of Minitab software at a significance level of 0.05. The results of the analysis show that the calculated t value is greater than the t table (5.703 > 1.67) and the P-value is smaller than 0.05 (0.000 < 0.05), so H₀ is rejected. Thus, it can be concluded that the use of Articulate Storyline learning media has a significant effect on the mathematics learning outcomes of class VIII students of SMP Negeri 5 Padang Panjang.